Scouting as a Means of Fostering Discipline of SMP N 9 Samarinda Students - Lestari, Indah Dwi; Suryaningsi, Suryaningsi; Asnar, Asnar; Majid, Novita (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to examine in depth the role of scouting activities in fostering student discipline at SMP Negeri 9 Samarinda. The background of this study is the low awareness of student discipline which can be seen from tardiness, incompleteness of attributes, and violation of rules even though school sanctions have been applied. Scouting was chosen as an informal media that is loaded with the values of discipline, responsibility, cooperation, and toughness, so that it is considered effective as a character building strategy. This research uses a qualitative descriptive method with direct observation techniques, interviews with coaches, schools, students, and documentation of activities such as attendance and competition reports. The results of the study show that activities such as routine exercises, marching, outbound, camps, and skill competitions are able to increase students' awareness of discipline, neatness, and compliance with rules. The habituation method through weekly exercises, ceremonies, educational sanctions, and awarding achievements has proven to be effective in instilling discipline in a sustainable manner. The pattern of positive and negative reinforcement forms the intrinsic motivation of students so that they obey not because of fear of punishment, but because of personal awareness. However, this study also found challenges such as the variability of coach commitment, limited facilities and funds, and the lack of systematic evaluation of student character. Therefore, it is recommended that schools increase the frequency and variety of scouting activities, establish cooperation with parents and external institutions, and train coaches in effective activity management and sanctioning.